Computational intelligence for missing data imputation, estimation and management [ knowledge optimization techniques - Marwala, Tshilidzi , 1971- (Information Science Reference, 2009)
"This book is for those who use data analysis to build decision support systems, particularly engineers, scientists and statisticians"--Provided by publisher.